2020
DOI: 10.1039/d0ra06010k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2D cobalt oxide nanosheets using a room temperature liquid metal

Abstract: A RT liquid metal based on Ga can be used as a synthesis medium for creation of 2D nanosheets of cobalt oxide via expulsion of the sheets from the liquid metal surface into an acidic aqueous solution. The 2D nanosheets are shown to be active for OER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…However, non‐favorable oxides such as CoO may form over Ga 2 O 3 via controlling the solution pH into which the material is ejected. [ 85 ] The presence of the diluted acid leads to the dissolution of any gallium oxides that are formed, subsequently promoting the formation of CoO x nanosheets in solution. Besides, Ga 2 O 3 has a similar reduction in the Gibbs free energy with TiO 2 , revealing that the surface of Ga–Ti alloy should be dominated by TiO 2 , and a few Ga 2 O 3 as a side product.…”
Section: Fabrication Strategies Of 2d Metal Oxides Via Liquid Metalsmentioning
confidence: 99%
“…However, non‐favorable oxides such as CoO may form over Ga 2 O 3 via controlling the solution pH into which the material is ejected. [ 85 ] The presence of the diluted acid leads to the dissolution of any gallium oxides that are formed, subsequently promoting the formation of CoO x nanosheets in solution. Besides, Ga 2 O 3 has a similar reduction in the Gibbs free energy with TiO 2 , revealing that the surface of Ga–Ti alloy should be dominated by TiO 2 , and a few Ga 2 O 3 as a side product.…”
Section: Fabrication Strategies Of 2d Metal Oxides Via Liquid Metalsmentioning
confidence: 99%
“…The bandgap analysis of 2D ITO corroborated the optical bandgap of 3.9 eV, revealing that the developed 2D ITO is 6.25 times more transparent than the monolayer of graphene. 128,137,138 It was also found that the sheet resistivity of the 2D transparent ITO lm is a function of the ITO layer number in the lm. 128 In fact, a continuous reprinting process led to the deposition of a bilayer ITO lm with much improved conductivity.…”
Section: The Squeeze Printing Techniquementioning
confidence: 99%
“…In another research study, 2D cobalt oxide nanosheets were synthesized via injection of O 2 gas inside a liquid galinstan droplet containing various weight percentages of a cobalt alloy. 138 To prevent the formation of gallium oxide nano-akes, HCl was introduced into an aqueous solution to minimize the formation of natural surface oxide layers and to control the pH of the solution at an acidic level. 138 It is well known that acids will dissolve natural gallium oxide on the surface of a galinstan alloy containing elemental Co.…”
Section: Reactive Environment For Synthesis Of 2d Lmsmentioning
confidence: 99%
See 2 more Smart Citations